2018
DOI: 10.1002/ptr.6033
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine for depression and anxiety:Asystematic review with assessment of potential psycho‐oncologic relevance

Abstract: Anxiety and depression are prevalent among cancer patients, with significant negative impact. Many patients prefer herbs for symptom relief to conventional medications which have limited efficacy/side effects. We identified single-herb medicines that may warrant further study in cancer patients. Our search included PubMed, Allied and Complementary Medicine, Embase, and Cochrane databases, selecting only single-herb randomized controlled trials between 1996 and 2016 in any population for data extraction, exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 140 publications
3
113
0
9
Order By: Relevance
“…On the other hand, our results also suggested that chamomile can significantly affect mild to severe GAD cases in the short‐term period (2–4 weeks) with a lesser impact on the long‐term (8 or 26 weeks; Amsterdam et al, ; Awad et al, ; Keefe et al, ; Mao et al, ). Our results appear to be similar to the previous systematic reviews conducted by Yeung et al and Savage et al (Savage, Firth, Stough, & Sarris, ; Yeung, Hernandez, Mao, Haviland, & Gubili, ). All the studies identified in the two previous systematic reviews were included in our study (Amsterdam et al, ; Keefe et al, ; Mao et al, ) Moreover, we have performed a meta‐analysis of the anxiety outcome of GAD patients based on the HAM‐A scale rather than just reporting the results narratively.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, our results also suggested that chamomile can significantly affect mild to severe GAD cases in the short‐term period (2–4 weeks) with a lesser impact on the long‐term (8 or 26 weeks; Amsterdam et al, ; Awad et al, ; Keefe et al, ; Mao et al, ). Our results appear to be similar to the previous systematic reviews conducted by Yeung et al and Savage et al (Savage, Firth, Stough, & Sarris, ; Yeung, Hernandez, Mao, Haviland, & Gubili, ). All the studies identified in the two previous systematic reviews were included in our study (Amsterdam et al, ; Keefe et al, ; Mao et al, ) Moreover, we have performed a meta‐analysis of the anxiety outcome of GAD patients based on the HAM‐A scale rather than just reporting the results narratively.…”
Section: Discussionsupporting
confidence: 93%
“…with a better balance of benefits and potential harms [4], as has been confirmed for Hypericum perforatum, which is the active component of several marketed medicines.…”
Section: The Efficacy Of Saffron In the Treatment Of Mild To Moderatementioning
confidence: 77%
“…Due to the ever-increasing number of phytotherapeutic preparations possessing upright clinical evidence, the role of herbal medicines in the treatment of psychiatric disorders has become customary over the past years (34). These alternative products appear to be safer than traditional pharmacotherapy, with lower adverse effect occurrence rates (35). Moreover, a significant number of patients prefer herbal preparations for symptom relief to conventional drugs.…”
Section: Herbal Medicinesmentioning
confidence: 99%